2011
DOI: 10.1538/expanim.60.141
|View full text |Cite
|
Sign up to set email alerts
|

Histological Examination of the Relationship between Respiratory Disorders and Repetitive Microaspiration Using a Rat Gastro-Duodenal Contents Reflux Model

Abstract: Microaspiration due to gastroesophageal reflux (GER) has been suggested as a factor contributing to the development and exacerbation of several respiratory disorders. To explore the relationship between GER and respiratory disorders, we histologically examined the bilateral lungs of a rat gastroduodenal contents reflux model, which was previously used to investigate the histogenesis of Barrett's esophagus and esophageal carcinoma. GER was surgically induced in male Wistar rats. The bilateral lungs of the reflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…There are two possible mechanisms to explain the relationship between GER and reflux-related respiratory symptoms: a direct inflammatory effect through microaspiration,31 or an indirect effect through esophageal distension and vagal stimulation 13,32. Rosen et al13 reported that proximal reflux is strongly associated with respiratory symptoms (OR, 1.31; 95% CI, 1.01-1.69) and that 75% of non-acid reflux, compared with 8.8% of acid reflux, reaches the proximal esophagus in children with persistent respiratory symptoms and who take antacid medications.…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible mechanisms to explain the relationship between GER and reflux-related respiratory symptoms: a direct inflammatory effect through microaspiration,31 or an indirect effect through esophageal distension and vagal stimulation 13,32. Rosen et al13 reported that proximal reflux is strongly associated with respiratory symptoms (OR, 1.31; 95% CI, 1.01-1.69) and that 75% of non-acid reflux, compared with 8.8% of acid reflux, reaches the proximal esophagus in children with persistent respiratory symptoms and who take antacid medications.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although studies using our model of aspiration under anesthesia preclude more frequent aspiration, it seems likely that such studies may be very worthwhile. One possible means by which this may be accomplished is the induction of aspiration using a surgical approach [38]. However, such models cannot distinguish between the effect of actual aspiration and the effects of vagally-mediated reflex bronchospasm, which does not require aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…Appel et al (1) described the characteristics of the inflammatory response to chronic localized aspiration in rats whereas other investigators studied inflammation and fibrosis as outcomes at the end of protocols involving repetitive tracheal instillations of specific components of gastroduodenal contents (6,27). In addition, a surgical gastroduodenal contents reflux model has been developed to study airway effects (22). However, little is known about the time course of ECM changes during repair following chronic aspiration of gastric contents as those that have been described in other models of lung injury that evolve to fibrosis (30,35).…”
Section: Introductionmentioning
confidence: 99%